The concept of brand building process towards Vietnamese enterprises in the new era - Khanh Tuan, Vuong; Palaniappan, Sellappan (Marketing & Menedzsment, 2021)
THE AIMS OF THE PAPER As customers' needs are changing very rapidly, it is important for all growing enterprises not only to provide high-quality products/services but also to exceed the customers’ own expectations. Businesses need to change their marketing strategies to meet their customers’ expectations, including brand management strategy which plays a vital role in conveying the value of products/services to potential customers. To increase the competitive advantage of Vietnamese enterprises in integrating with the international economy, there is a need for innovation in brand management. It is necessary to provide the concept of the brand-building process to the businesses as overview; it is vital to apply it in the planning and implementation of brand management strategy in Vietnamese enterprises. METHODOLOGY This empirical study has been analyzed and is presented for the future use in the concept of brand building process towards Vietnamese Enterprises. This paper was conducted in two phases. In the first phase, the researcher uses a qualitative approach to interview experts, administrators, who conduct the research on the marketing field to discuss how the phases and procedures to build a brand for the new era for Vietnamese enterprises. There were 12 experts selected to discuss to gain the model for the concepts in brand building for this new era. There were (6) questions discussed with the experts to collect the research data relative to the brand building process. Preceding this, the researcher gathered the opinions of these marketing experts to gain an overview of the process to create branding building. MOST IMPORTANT RESULTS The researcher summarizes four critical phases in the brand-building process for Vietnamese businesses in the new era. There are four necessary phases in building a brand as follows: (1) brand identity, (2) brand awareness, (3) brand love, and (4) brand loyalty. Depending on the strategy of the business that can be applied in the brand-building process in each individual phase or the brand- building process can combine four phases concurrently in building a branding strategy. RECOMMENDATIONS From the outcomes of this study, the researcher recommends that practitioners, as well as scholars can apply and research based on this study to improve in branding for businesses for sustainable development purposes in the new era.